Türk Sanatında Seramik Fırınlarının Tipolojik Evrimi ve Teknolojik Etkileşimler. - Özkul Fındık, Nurşen; Kalay, İbrahim Semih (Electronic Turkish Studies)
This study examines the typological evolution and technological interactions of ceramic kilns in the Turco-Islamic world over a broad period spanning from the 7th to the 20th century. The research challenges the common and simplistic thesis that there was a linear evolution in kiln typology from circular to square plans. Instead, it argues that kiln typology was shaped by a more complex interplay of technological continuity, functional specialization, and creative synthesis. The fundamental kiln technology in this tradition is the circular or oval-plan updraft kiln, a legacy inherited from Mesopotamia via Roman and Byzantine Anatolia. This model remained the dominant type for centuries, as evidenced by archaeological findings in Seljuk centers such as Konya and Ahlat. While the influence of Chinese ceramics was profound, it was more aesthetic than technological. Rather than adopting China's high-firing dragon kilns, Islamic artisans ingeniously innovated in materials by developing fritware (stonepaste) bodies, which they adapted to their existing updraft kiln technologies to mimic the appearance of porcelain. Early Islamic centers, such as Pechina in al-Andalus and Termez in Central Asia, reveal the simultaneous use of circular and rectangular kilns within the same workshops, suggesting that different kiln types were used for specialized production lines. The Ottoman period represents the zenith of this technological synthesis. While the kilns of Iznik largely continued the established Anatolian tradition, the traditional Kütahya kiln emerges as a sophisticated hybrid structure: it combines the thermal efficiency of a circular inner chamber with the structural stability of a square exterior and incorporates specialized frit-settling troughs inherited from Seljuk-era Iran. This demonstrates that the evolution of the Turco-Islamic kiln was not a linear progression but a dynamic process of adaptation, fusion, and innovation driven by the need to meet specific artistic and production demands.